Noise Levels at Mosul City's Academic Medical Centers (Texas Journal of Medical Science, 2024)
This study is to quantify the noise levels at Mosul City's teaching hospitals, break those levels down by time of day and night, and compare the noise levels on weekdays and weekends. We used digital sound level meters to assess the noise levels at the Iben-Sena, Aljamhory, Alkhansa'a, and Alsalam Teaching Hospitals. Material and methods: We measured and categorized the noise levels in each hospital at nine in the morning, eleven in the afternoon, two in the evening, five in the evening, and seven in the evening. The medical ward is involved in all hospitals, but Aljamhory Teaching Hospital adds the important areas to that future research may use it as a baseline. Results: The study included a total of 556 readings obtained from all participating hospitals. We calculate the average of all measurements after selecting a parameter, the equivalent sound level (Leq) in decibels (dBA). Plus, you can see how much noise there is on weekdays (Sunday through Thursday) compared to weekend days (Friday and Saturday). Acurrent experiment is investigating the origin of background, noise at academic medical centers.